1997
DOI: 10.1074/jbc.272.18.12189
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of a Broad Spectrum of Extracellular Matrix Proteins by Human Macrophage Elastase

Abstract: Macrophage elastase (ME) was originally named when metal-dependent elastolytic activity was detected in conditioned media of murine macrophages. Subsequent cDNA cloning of the mouse and human enzyme demonstrated that ME is a distinct member of the matrix metalloproteinase family. To date, the catalytic parameters that describe the hydrolysis of elastin by ME have not been quantified and its activity against other matrix proteins have not been described. In this report, we have examined the action of purified r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
204
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(208 citation statements)
references
References 32 publications
4
204
0
Order By: Relevance
“…This process may be facilitated by the lack of inhibitors of cathepsin D in mammalian tissues. Elastin, fibronectin, laminin, collagen IV, proteoglycan, inactivation of ␣ 1 -proteinase inhibitor [104] Classification by preferred substrate(s)…”
Section: Aspartic Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This process may be facilitated by the lack of inhibitors of cathepsin D in mammalian tissues. Elastin, fibronectin, laminin, collagen IV, proteoglycan, inactivation of ␣ 1 -proteinase inhibitor [104] Classification by preferred substrate(s)…”
Section: Aspartic Proteinasesmentioning
confidence: 99%
“…In vitro studies have demonstrated that reactive oxygen species released by activated leukocytes can inactivate serpins (␣ 1 -proteinase inhibitor and SLPI) as well as ␣ 2 -macroglobulin [98][99][100][101]. Serpins are also susceptible to proteolytic inactivation by several classes of proteinases: (1) several MMPs (MMP-1, MMP-3, MMP-7, MMP-8, MMP-9, and MMP-12) can inactivate ␣ 1 -proteinase inhibitor, ␣ 1 -antichymotrypsin, and also ␣ 2 -macroglobulin [25,26,[102][103][104]; (2) the serine proteinase, HLE, can inactivate its cognate inhibitor (␣ 1 -proteinase inhibitor) [105] and PAI-1 [106]; (3) cathepsin B (a cysteine proteinase) can inactivate ␣ 1 -proteinase inhibitor [107]; and (4) several bacterial proteinases can inactivate ␣ 1 -proteinase inhibitor and SLPI [108]. It is also noteworthy that serine proteinases can proteolytically inactivate TIMPs [109].…”
Section: Inactivation Of Proteinase Inhibitorsmentioning
confidence: 99%
“…As suggested by its trivial name (metalloelastase), MMP-12 is clearly the most active MMP against elastin [38] although it can cleave many of the other components of the extracellular matrix such as fibronectin, fibrillin-1, laminin, entactin, type IV collagen fragments, chondroitin sulfate and heparan sulfate proteoglycans and vitronectin [35,39,40]. However, MMP-12 can not significantly degrade fibrillar collagen or gelatin [39]. In vivo, MMP-12 has the ability to activate other MMPs such as pro-MMP-2 and pro-MMP-3, which, in turn, can activate pro-MMP-1 and pro-MMP-9.…”
mentioning
confidence: 99%
“…7 Although the major substrate for MMP-12 is elastin, MMP-12 is able to degrade a broad spectrum of substrates such as type IV collagen, fibronectin, laminin, vitronectin, proteoglycans (PGs), chondroitin sulfate, myelin basic protein, ␣-1-anti-trypsin, and plasminogen. 8,9 Moreover, human and mouse MMP-12 undergo self-activation through autolytic processing, and recombinant rabbit MMP-12 has been shown to activate other MMPs such as MMP-2 and MMP-3. 5 Importantly, MMP-12 expression of macrophages is highly regulated by inflammatory mediators such as GM-CSF, MCP-1, 10,11 and CD40 ligands, 12 suggesting that in many inflammatory processes, once MMP-12 is up-regulated, there is a cascade of activation of other MMPs that leads to extracellular matrix degradation.…”
mentioning
confidence: 99%